2020
DOI: 10.3390/ijms21238946
|View full text |Cite
|
Sign up to set email alerts
|

The Gut-Muscle Axis in Older Subjects with Low Muscle Mass and Performance: A Proof of Concept Study Exploring Fecal Microbiota Composition and Function with Shotgun Metagenomics Sequencing

Abstract: The gut microbiota could influence the pathophysiology of age-related sarcopenia through multiple mechanisms implying modulation of chronic inflammation and anabolic resistance. The aim of this study was to compare the fecal microbiota composition and functionality, assessed by shotgun metagenomics sequencing, between two groups of elderly outpatients, differing only for the presence of primary sarcopenia. Five sarcopenic elderly subjects and twelve non-sarcopenic controls, classified according to lower limb f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 74 publications
3
78
0
2
Order By: Relevance
“…prausnitzii produces butyrate [ 66 , 71 ]. Recently, the relationship between depletion of this gut microbiota member and the presence of sarcopenia has been explored in a small groups of older adults [ 72 ], the shotgun metagenomic sequencing approach used for this study allowed to identify a depletion in microbial genes involved in diverse metabolic pathways mainly SCFA synthesis, carotenoid and isoflavone biotransformation and amino acid interconversion in sarcopenic adults when compared to non-sarcopenic counterparts [ 72 ]. Although it is not possible to determinate if these metabolic pathways are specifically related to the abundance of F .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…prausnitzii produces butyrate [ 66 , 71 ]. Recently, the relationship between depletion of this gut microbiota member and the presence of sarcopenia has been explored in a small groups of older adults [ 72 ], the shotgun metagenomic sequencing approach used for this study allowed to identify a depletion in microbial genes involved in diverse metabolic pathways mainly SCFA synthesis, carotenoid and isoflavone biotransformation and amino acid interconversion in sarcopenic adults when compared to non-sarcopenic counterparts [ 72 ]. Although it is not possible to determinate if these metabolic pathways are specifically related to the abundance of F .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several studies also suggest that F. prausnitzii produces butyrate [66,71]. Recently, the relationship between depletion of this gut microbiota member and the presence of sarcopenia has been explored in a small groups of older adults [72], the shotgun metagenomic sequencing approach used for this study allowed to identify a depletion in microbial genes involved in diverse metabolic pathways mainly SCFA synthesis, carotenoid and isoflavone biotransformation and amino acid interconversion in sarcopenic adults when compared to non-sarcopenic counterparts [72]. Although it is not possible to determinate if these metabolic pathways are specifically related to the abundance of F. prausnitzii or another gut microbial member, it is of interest that numerous studies involving active people report an increase of this Firmicutes member, future studies in this field should aim to study the relationship between the metabolic function of F. prausnitzii and physical activity in different age groups [73,74].…”
Section: Plos Onementioning
confidence: 99%
“…The Ruminococcus, Roseburia and Clostridiaceae were positively correlated with the improvement of the neurological status-specifically, by manifesting positive association with the Rivermead Mobility Index and negative association-with the Rankin scale. Among them, Roseburia known for its metabolic capacity of producing short-chain fatty acids has been reported to be depleted in fecal samples of sarcopenic subjects [ 32 ]. In addition, we found that the increased abundance of Clostridiaceae in the gut was associated with the positive neurological dynamics in the CCI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, microbiota transplantation could rescue the phenotype, pointing to a direct influence on skeletal muscle [ 110 ]. However, due to the high interindividual variability observed in the human microbiota composition, additional controlled studies with larger sample sizes are needed to rule out a causal link [ 109 , 111 , 112 ]. Additional reports suggest a possible role of the gut microbiota in the regulation of PPARs and the peripheral muscle circadian clock [ 113 , 114 ].…”
Section: Crosstalk Between Skeletal Muscle and Other Organs In Cacmentioning
confidence: 99%